2013
DOI: 10.1111/isqu.12092
|View full text |Cite
|
Sign up to set email alerts
|

Martial Law? Military Experience, International Law, and Support for Torture

Abstract: A large body of work points to diverging civil–military views on the initial decision to use force, yet there is little sense if similar differences hold over appropriate conduct in the midst of armed conflict. The rise of international laws governing behavior during war has similarly raised the question of whether these rules can shape the beliefs of various domestic actors. This paper seeks to address both gaps in the literature by leveraging the use of experiments embedded in a pair of US national surveys t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…13 We also expect variation in the military service variable even under Israel's compulsory military service laws, since there are notable exceptions to service. Military service predicts attitudes toward the use of force (Wallace 2014). We also collect data on respondents' primary news source, including television, print, online, radio or podcasts.…”
Section: Group Status Manipulationsmentioning
confidence: 99%
“…13 We also expect variation in the military service variable even under Israel's compulsory military service laws, since there are notable exceptions to service. Military service predicts attitudes toward the use of force (Wallace 2014). We also collect data on respondents' primary news source, including television, print, online, radio or podcasts.…”
Section: Group Status Manipulationsmentioning
confidence: 99%
“…These studies have generally shown that the legal component of international human rights and humanitarian law violations can shift popular opinion. That is, respondents who are told about an immoral state practice are significantly less likely to support that practice (or more likely to support action to prevent it) if they are also told that the practice violates international law (Wallace 2013(Wallace , 2014Chilton 2014). These findings are remarkable in their implication that international law qua law can have an observable, normative pull on the electorate.…”
Section: Public Opinion and International Law 21 International Law'smentioning
confidence: 99%
“…This article contributes to at least two different bodies of research. First, we add to the growing experimental literature on the effect of international law on popular opinion (Tomz 2008;Wallace 2013Wallace , 2014Chilton 2014). These studies have generally found that respondents are less likely to support policies that violate international law, suggesting that they value international law qua law.…”
Section: Introductionmentioning
confidence: 99%
“…This article contributes to at least two different bodies of research. First, we add to the growing experimental literature on the effect of international law on popular opinion (Tomz 2008; Wallace 2013, 2014; Chilton 2014). These studies have generally found that respondents are less likely to support policies that violate international law, suggesting that they value international law qua law.…”
Section: Introductionmentioning
confidence: 99%